REPRESENTAÇÃO SOCIAL DE ENFERMEIROS E ACADÊMICOS DE ENFERMAGEM SOBRE A PERCEPÇÃO DOS RISCOS LABORAIS A QUE ESTÃO EXPOSTOS EM UNIDADES DE ATENÇÃO Á SAÚDE - Azucena del Valle Rojas; Adenícia Custódia Silva e Souza; Cristina ARREGUY- Sena (Universidade Federal de Goias, 2000)
Social representation of nurses and academics of nursing about the perception of the works risks in which they are exposed in units of health care attendance services. Analyzing 18 people's perception among nurses and academics of nursing on the risks in which they are exposed in the hospital environment and in primary attendance services to the health, we used the social representations as a methodological referential. We used the analysis of content proposed by Bardin and we recorded the interviews starting from an specific question. "Cartoon" technique and the free drawings technique were used to collect data, and the methodological course is explicit in seven steps. It could be noticed as risks, the institutional relationships, professional and personal relationships. The work conditions worsened by the professional acquaintance in serious situations and of proximity with the death. The participants were considered not very valued in its potentiality, since the relationships of power and a very strict hierarchy prevail. The medical hegemony and the financial conditions were noticed as the base of the institutional decisions.